The Physicochemical and Cytotoxicity of Emulsified Virgin Coconut Oil and Its Molecular study on COX-2 Inhibition: A Computer Aided Drug Design Approach - Swen Jack, Kho; Mohd Razip, Asaruddin; Showkat Ahmad, Bhawani (UNIVERSITI MALAYSIA SARAWAK, 2023)
Virgin coconut oil (VCO) has attracted many interests for research due to it having outstanding health benefits and potential for cosmetics, drugs, and nutraceuticals. Virgin coconut emulsion (VCE) is an advanced, nanosized form of VCO with increased bioavailability. The oil-in-water type of emulsified VCO has become soluble in water, thus, increasing the conversion rate of triglycerides to lauric acid, monolaurin, and other vital derivatives. This study is to formulate a novel oil-in-polyol type VCE with high grade solubility, versatile for making supplements, cosmetics, and as a drug delivery system against inflammation. GCMS determined the most suitable VCO to be used in the formulation whereby the optimal VCE formulation (1:4) was found with SC ratio of 32:50 via constructing Pseudo-ternary phase diagram. It passes the thermodynamic and shelf stability test followed by achieving great polydispersity index (0.2737), particle size distribution (46.08 nm), zeta potential score (-20.07). Drug design concluded with the results obtained showing that the monolaurin (-7.58 kcal/mol) has strong interactions with COX-2 protein to disrupt its function due to significant hydrogen bonds (5) and hydrophobic interactions (10) with amino acid residues present in the target protein’s active site. These results displayed positive anti-inflammatory result of monolaurin in VCE as new promising drug candidate against inflammation based on CADD.